Microfinance for poverty alleviation: do transnational initiatives overlook fundamental questions of competition and intermediation? - Arp, Frithjof; Ardisa, Alvin; Ardisa, Alviani (United Nations Conference on Trade and Development, 2017)
Numerous microfinance initiatives around the world aim to alleviate poverty in developing countries. However, debate persists about their effectiveness and sustainability – a concern for transnational corporations and the international business community, which contribute about $9.4 billion to microfinance funding. In this policy-oriented article we aggregate findings from two studies in Indonesia that help explain why moneylending can still thrive when low-interest microfinance is widely available and why the poorest borrowers benefit less than the less-poor. To avoid methodological debates about validity, we interview market participants and triangulate the perspectives of borrowers with those of formal and informal lenders. Importantly, our research includes current and past borrowing from formal and informal sources, prompting participants to draw comparisons. We find that the importance to borrowers of key characteristics of informal lending is insufficiently recognized and that inappropriate human resource management and informal intermediation are significant problems. The latter can be an unintended consequence of formal microfinance: The availability of formal low-interest microfinance creates informal intermediation opportunities for entrepreneurs, often developing from casual intermediation into systematic deception. We discuss implications for microfinance policy with reference to the United Nations Sustainable Development Goals and offer suggestions for further research.